OPTIMALISASI POTENSI BUAH KAWISTA SEBAGAI UPAYA PENGEMBANGAN DESA MANDIRI DI DESA DUREN KECAMATAN KLARI KABUPATEN KARAWANG - Rulliannor Syah Putra; Harti Widya Astuti; Nadia Almira Jordan (Jurnal Abdi Insani, 2023)
Independent village is a program from West Java Province to empower villages to fulfill their own needs, reduce dependency on assistance from the Government through increasing the potential of natural resources, human resources, and maintaining the local culture of the community. The achievement of independent villages is supported by the existence of West Java Village Patriots who serve as village assistants, the form of activities can be through assistance, direction, organizing and facilitating village activities. The target village is Duren Village which is an independent village based on a fairly high IDM score. Kawista fruit was chosen as the flagship program because kawista products have won competitions at the West Java Province level and have local drivers who understand the processing process for sustainability to become kawista production centers. The method of implementing activities carried out with the learning by doing system. The activities carried out started from discovering village potential, sharing knowledge for those who have experience, forming processing groups, conducting kawista fruit nurseries, creating social media and promotion through MSME activities. The results that have been obtained during the activity are kawista fruit as the superior product of the village, the community has knowledge in processing kawista fruit, increasing a sense of togetherness, the spirit of mutual cooperation in processing kawista fruit, the community can do kawista fruit nurseries, how to make and operate media social media, as well as how to make an NIB (Business Identification Number) as a condition for participating in MSME festival activities. Meanwhile, the results achieved in the long term are that the community has the skills, understanding, harmony, independence so that the Duren Village community is able to create a Kawista Processed Industrial Center which can be marketed starting from the West Java region, outside West Java Province and even to foreign countries. Therefore, the potential of kawista fruit needs to be optimized together with the community so that it can support the development of independent villages through kawista fruit.